Budaya Kritik Ulama Hadis Perspektif Historis dan Praktis - Umar, Atho'illah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2011)
Sunnah, as the second source after Koran had been through several hard priod which stems from slander, emerge in the midst of Muslims since the death of caliph Othman b. ‘Affan. During that, the Sunnah of the Prophet become a tool for political infighting and it arose multi fanaticism, starting from the fanaticism of madhhab, race, class, and other fanaticism along with the break up of the Muslims into sects. This makes the Sunnah ainted. It was difficult to distinguish between an authentic hadith, da‘îf even mawdû‘. It is difficult to distinguish whether the transmitters are thiqah, free from fanaticism, or other tendency, which caused the narrators unable to maintain the integrity of Sunnah. Since the codification campaign echoed the hadith, the scholars began the unification and selection of traditions in various ways, all were concentrated on the activities of criticism as an effort to authenticate hadith, chains. So, the common question of tradition at the time was whether the isnâd valid, whether the matn certainly valid as well. This paradigm emerged different disciplines related to the study, such as science of isnâd, al-jarh wa al-ta‘dîl, al-tabaqât, al-‘ilal and so forth